2009
DOI: 10.1093/qjmed/hcn177
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethnicity on the prevalence of diabetes and associated chronic kidney disease

Abstract: Significant disparities exist between the major ethnic groups in both disease prevalence and management. Future studies examining the management of CKD need to take variation by ethnicity into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 22 publications
3
71
0
Order By: Relevance
“…3 Ethnicity is known to influence the prevalence of diabetes, albeit in a complex manner, with many overlapping co-factors. 1,[7][8][9][10][11] In the UK, the prevalence of diabetes within a population of South Asian background is higher than the general population. 10,11 Locally, 74.9% of the NHS Bradford City clinical commissioning group Table 2 The effect of treatment on VA for the n = 9 eyes that were naïve to any prior treatment at baseline The effect of treatment on VA and CMT for the n = 42 eyes that had received treatment for diabetic retinopathy or maculopathy (macular laser, pan-retinal photocoagulation, intravitreal Avastin, or Triamcinolone) prior to intravitreal ranibizumab.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Ethnicity is known to influence the prevalence of diabetes, albeit in a complex manner, with many overlapping co-factors. 1,[7][8][9][10][11] In the UK, the prevalence of diabetes within a population of South Asian background is higher than the general population. 10,11 Locally, 74.9% of the NHS Bradford City clinical commissioning group Table 2 The effect of treatment on VA for the n = 9 eyes that were naïve to any prior treatment at baseline The effect of treatment on VA and CMT for the n = 42 eyes that had received treatment for diabetic retinopathy or maculopathy (macular laser, pan-retinal photocoagulation, intravitreal Avastin, or Triamcinolone) prior to intravitreal ranibizumab.…”
Section: Discussionmentioning
confidence: 99%
“…1,[7][8][9][10][11] In the UK, the prevalence of diabetes within a population of South Asian background is higher than the general population. 10,11 Locally, 74.9% of the NHS Bradford City clinical commissioning group Table 2 The effect of treatment on VA for the n = 9 eyes that were naïve to any prior treatment at baseline The effect of treatment on VA and CMT for the n = 42 eyes that had received treatment for diabetic retinopathy or maculopathy (macular laser, pan-retinal photocoagulation, intravitreal Avastin, or Triamcinolone) prior to intravitreal ranibizumab. Table 3 Comparison of age, visual acuity, and CMT data for subjects with poorer baseline VA (o55 letters) and better baseline VA (≥55 letters) and for subjects with thinner (o500 μm) and thicker (≥500 μm) baseline CMT (CCG) population is South Asian, 14 where prevalence of known diabetes is 8.9% compared with 6.7% in similar sized CCGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dreyer et al performed a cross-sectional study of 34,359 patients with diabetes in three primary care trusts in the UK. 24 They found that the prevalence of people with an eGFR of <45 mL/min was 5.4%. However, this may be an underestimate because the study population contained a significant number of non-white individuals (who have a lower prevalence of CKD stage 3).…”
Section: The Importance Of Glycaemic Controlmentioning
confidence: 99%